Analisis Implementasi Kebijakan Insentif Pajak Kendaraan Bermotor Dimasa Pandemi Covid-19 Dalam Meningkatkan Penerimaan Pajak Daerah Pada Samsat Cikokol Kota Tangerang Tahun 2020-2021 - Dinda Dwi Lestari; Martina Safitri (Jurnal Ilmu Administrasi Publik, 2022)
This study discusses the elimination of motor vehicle tax administration sanctions in the Cikokol area of Tangerang City. The purpose of this study is to analyze the motor vehicle tax incentive policy during the Covid-19 pandemic in order to increase local tax revenue at Cikokol SAMSAT office in 2020-2021. Motor vehicle tax is a type of tax levied on the ownership of a motor vehicle. The low compliance of taxpayers in paying motor vehicle taxes is the cause of the non-optimal tax revenue. This research was conducted using descriptive qualitative research methods with data collection techniques of interviews, observation, and documentation. The results showed that the motor vehicle tax administration sanction elimination program was quite effective, but not significant in increasing local tax revenues at Cikokol SAMSAT office. Several factors that affect the compliance of motorized vehicle taxpayers in the Cikokol SAMSAT area of Tangerang City are the awareness of taxpayers in paying their obligations, economic level of motorized vehicle taxpayers, lack of updated facilities and infrastructure, quality of applications, and network improvements. Efforts that need to be made to improve the compliance of motorized vehicle taxpayers are to continue campaigning to the public both online and offline about motor vehicle taxes and involve community leaders to conduct persuasive campaigns.